Study of the microstructure of collapsible soil treated with the potassium chloride - Bahloul, Ouassila; Abbeche, Khelifa; Bahloul, Azeddine (Journal of Applied Engineering Science & Technology, 2016)
The collapse of soils is a very complex phenomenon that involves a large number of intrinsic and environment parameters. This research aims to try to better understand the causes of collapse of soils and propose solutions to improve them and limit subsidence at least to an acceptable level. From a soil sample reconstituted in the laboratory, composed of a mixture (80% sand and 20% kaolin), we have shown the benefit of additions of salt solutions such as KCl. Analyses with scanning electron microscope and spectroscopy energy dispersive X-ray revealed microstructural changes and a significant interaction between clay particles and potassium chloride. The K + cation is easily embedded in the pores and promotes the formation of a dense and compact material.
Keywords: Collapsible soil; Compaction energy; Chemical treatment; Oedometer